Developing of Teaching Materials: Using Animation Media to Learning English Vocabulary For Early Childhood - Siregar, Ayu Sartika Br; Tobing, Endang Golis L; Fitri, Nur Rizka (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
Given the importance of vocabulary, teachers must ensure teaching media that can help students learn English vocabulary more easily. In addition, it must equip them to learn in an interesting way so that they are more enthusiastic about the coaching and studying process. One of the many learning media that can be applied for learning English is video. Thus, this study will explain how animated media can help with vocabulary learning for early childhood and the uses and benefits of animated media. This study uses document analysis as the main way to generate arguments in this article, such as Teaching English documents, articles, and books, and document articles from national and international online publications. Based on the research, it may be evident that the software of lively motion pictures contributes to students' vocabulary mastery. The results showed that students can easily recognize the given words because they learn by using animated videos because they can not only display written words but also pictures.